Pengaruh Teknologi Internet Dalam Perkembangan Karakter Siswa SMPN 3 Jember - Zhidan Z. Putra; Lutfiaul Fuddah; Rini Indriani; Rahmah Wulandari; I Ketut Mahardika; Rizka Elan Fadilah; Firdha Yusmar (Peneliti.net, 2022)
This study aims to determine how influential internet technology is on the character development of students in a junior high school institution conducted at SMPN 3 Jember. In this study we use qualitative methods. Internet technology has a very big influence on all aspects. One aspect of internet technology is information technology where the existence of internet technology in information makes the era of globalization where the era is very easily accessible resulting in vulnerability, especially to the character development of junior high school students. It can be said that if information through internet technology is very easily accessible, it will have a bad effect on character development. The qualitative method used in this research is the study of literature, and a sociological approach and the application of behavioral psychology theory.